A study of effective marketing strategies on hand tuft carpet product towards individual consumer end - market / Intan Syafinaz Mat Shafie - Mat Shafie, Intan Syafinaz (1999)
The objective of this study are to seek potential opportunity for CIMB to emphasize on hand tuft carpet market, gather information on major factors that will affect individual consumer buying behaviour to purchase it and also to find the effective marketing strategy for hand tuft carpet. In addition, there are recommendations for CIMB to produce hand tuft carpet and ways of predicting its market demand. The target population of the study was conducted in Subang USJ area. Key strategy to gather data is through questionnaires. 100 questionnaires were randomly distributed with the use of cluster sampling. SPSS has been used to process and analyze the data. It is believed that every carpet manufacturer’s has their own product’s uniqueness. The difference between them is on how the manufacturer itself provides the services to the customers. As such, company’s promotion through attractive services are the best to implement.